Peningkatan Pemahaman Perkembangan Bahasa Anak di Kid Care Children Therapy Centre - Oktariani Oktariani; Windy Rainata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Language development is one form of development that must be considered in the development of children. Language barriers in children will affect other aspects of development, including developments in social skills and learning abilities. As children get older, the developmental tasks of children become more complex. This language development disorder can be found in several psychological disorders, including Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD). Kid Care Children Therapy Center is a therapy center that has clients with children with various disorders including ASD and ADHD. Therefore, it is important to provide material on children's language development, so that parents get information about the right stimulation for children with language development barriers. Based on the analysis above, the subjects involved in this community service are the parents of clients who are involved in therapeutic activities at the Kid Care Children Therapy Center. This activity was held on Thursday, March 25, 2021 in the form of psychoeducation and was attended by 17 participants. Based on the evaluation results, it can be said that this activity provides benefits as a forum to increase the knowledge of parents with special needs, especially related to the stimulation needed for their children. The enthusiastic response of the participants can be seen from the large number of questions asked by the participants. Participants also felt the benefits that could be applied directly related to their children so that some questions that were not related to child development also emerged, still within the psychological scope, such as the relationship between psychological assessments in children and the development period